Analisis Yuridis Tindak Pidana Pemerasan; Studi Kasus Berdasarkan Berita Acara Pemeriksaan (NO. POL: K/LP/550/III/2020/ POLRES.JKSEL) - Samara, Finsensius; Taolin, Laurenzo Ivander; Darmawan, Julian Putra; Pantur, Elisabet Nanda; Una, Ketrinia Marsela Tawa; Bimolo, Kristinia Maria Yosefa (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
This research analizes the crime of extrotion based on the the examinition report (BAP) whit police number K/LP/550/III/2020/POLRES.JKSEL dated march 13,2020.extortion as regulated in article 368 of the criminal code, is a crime against property that emphasizes the act of coercion thru violence or the threat of violence.the research uses a normative judical method whit a legislative and conseptual approach, analizyng the police investigation report (BAP)thtu a descritive method to assessthe suitabillity of the case proceeding to trial. This case involves the suspect (A) treatening the victim (F) usang a sharp weapon, a tiger claw,with theartening words that caused fear, leading the victim to hand over RP 1.000.000. the analysis results show that all elements of article 368 paragraph (1) of the criminal code are met, including objektive elements (ceorcive acts, violence/thearths of violence, and surrender of goods) and subjektive elements (the intention to benefit oneself unlawfully). Based on the completeness of the avidence,including the victim’s statement, the suspect’s confession, and the sharp weapon as physical evidence,this case is suitable to proceed to trial. The group analysis concluded that the suspect was proven guilty and sentenced to 3 years in prison, considering aggravating and mitigating factors, including the absence of phsycal injury, the suspect’s remorse, and emotional state as a trgger for the incident.